Alcune considerazioni sulla funzione della tecnologia nella psicoterapia online - Fargnoli, Domenico; Montanaro, Dori (Il sogno della farfalla, 2021)
The use of online psychotherapy has revealed to be fundamental in order to ensure continuity of psychotherapeutic treatments. These would have otherwise been interrupted due to the restrictions established to contain the COVID-19 pandemic. Over the last decades there has been a progressive diffusion of new technologies. Telemedicine has been largely and internationally recognised as a valuable tool in psychotherapeutic practice. Nevertheless in Italy there is still widespread ideological prejudice on the use of videoconference in online psychotherapy. The author therefore investigates and tries to elucidate the historical roots of this negative attitude towards technological innovation. In the case of video conference, digital devices play exclusively a supportive role by enabling communication between psychotherapist and patient without, however, modifying the conscious and non conscious content expressed in the rapport. In this paper it is underlined how, in order to understand the role of sensibility and corporeality in online psychotherapy, it is necessary to comprehend the distinction between body as object and body ad subject as postulated in the Human Birth Theory by Massimo Fagioli.